Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper focuses on the need and importance of fiscal integration for the Eastern Caribbean Currency Union (ECCU). The continued success of the currency union can be solidified by greater fiscal policy integration. Against the growing intensity of external shocks, country-level fiscal policies remain as the most important policy lever. Regional fiscal policy coordination could usefully supplement national policies in dealing with adverse shocks. Such coordination can potentially create fiscal and policy space along several dimensions. Internationally, fiscal integration takes many forms, depending on the interconnectedness of member economies and their willingness to give up fiscal autonomy. The analysis shows there is scope for tangibly improving tax incentives and rebalancing them toward those that are more effective, while using higher revenues to attract investment also through better infrastructure. Regional coordination could significantly support and accelerate those processes.